SECONDARY RAW MILK IN THE PRODUCTION OF FUNCTIONAL FOODS - Ivan Alekseevich Evdokimov; Irina Kirillovna Kulikova; Alena Romanovna Agirbova; Angela Victorovna Novoselskaya; Andrei Andreevich Smirnov (Вестник Северо-Кавказского федерального университета, 2022)
This article discusses the properties of the various components of milk, as well as methods for their use in the dairy production in order to obtain functional products.